Aboveground soil supports high levels of biological activity in oil palm plantations. Issue 4 (27th February 2020) - Potapov, Anton; Bonnier, Roman; Sandmann, Dorothee; Wang, Simin; Widyastuti, Rahayu; Scheu, Stefan; Krashevska, Valentyna
Abstract : Oil palm plantations are expanding rapidly throughout Southeast Asia due to increasing global food demand, thereby putting greater pressure on local ecosystems. These plantations usually replace rainforests, resulting in major losses of soil structure and fertility, and belowground biodiversity. However, despite causing soil degradation, oil palms may provide a novel microhabitat for soil biota in suspended soil that accumulates in the axils of cut palm fronds attached to the trunks of these trees. We examined soil communities belowground and in frond axils in a 16‐year‐old oil palm plantation in Sumatra, Indonesia. Community metabolism of small arthropods, nematodes, and testate amoebae (protists) per gram of soil was much higher in axils (suspended soil) than in belowground soil, and accounted for approximately 28% of total soil fauna metabolism at the plantation scale (considering the top 5 cm of soil). Preserving these aboveground microhabitats of suspended soil as hotspots of biological activity during plantation management may therefore partly offset the detrimental impacts of oil palm plantations on soil‐borne processes and biodiversity.